Pelatihan Sistem Manajemen Posyandu Berbasis Artificial Intelligence (AI) di Desa Danger - Ziyadatus Sholihatun; Linda Apriliana Maulida; Ria Oktavia; Arif Suriadi; Zul Hidayatullah (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Integrated Health Posts (Posyandu) play a crucial role in monitoring maternal and child health at the village level. However, manual administrative record-keeping at the Posyandu in Danger Village has hindered data recapitulation and the early detection of nutritional issues among toddlers. This community service initiative aimed to equip Posyandu volunteers with the skills to operate an Artificial Intelligence (AI)-based Posyandu Management System for monitoring the growth and development of children aged 0–59 months. The implementation employed a Participatory Action Research (PAR) approach comprising four stages: needs assessment, design of a WhatsApp-integrated system, dissemination and training, and mentoring and evaluation. The results demonstrated an improvement in the digital skills of 70 volunteers, enabling them to independently migrate from conventional data collection to a digital platform. Data for 62 toddlers was successfully entered, and the system's automated WhatsApp notification feature successfully delivered health assessment results to parents in real-time. The primary challenge identified was limited internet network infrastructure at the service location. The program highlights the importance of network infrastructure support from the village government to ensure the sustainability of healthcare service digitalization.